Evaluation of Macro Economic Policies of Pakistan (1950 -2008) - Tahir Mahmood, Hafeez ur Rehman; Shahnaz A. Rauf1 (Journal of Political Studies, 2008)
The economy of Pakistan performed quite well until the end of 1980s despite the major shift in policy stance by the economic managers, from a private sector led economy in the sixties to a nationalized economy in the 1970s and a shift towards liberalization, deregulation and denationalization in the decade of eighties. It was in the decade of nineties that Pakistan recorded the lowest GDP growth in South Asia and these were also the years when Pakistan experienced a series of adjustment and stabilization reforms. Towards the end of the nineties there were some signs of improvement in macro economic indicators. However, this improvement did not last long. Thus the economy of Pakistan has always remained under stress due to high fiscal and external sector imbalances, high aggregate demand, unsustainable GDP growth, high unemployment and poverty levels.